Outcomes of Implementing a Multidimensional Antimicrobial Stewardship Program in a Medical Ward in a Third-Level University Hospital in Northern Italy - Maria Mazzitelli; Daniele Mengato; Gianmaria Barbato; Sara Lo Menzo; Fabio Dalla Valle; Margherita Boschetto; Paola Stano; Cristina Contessa; Daniele Donà; Vincenzo Scaglione; Giacomo Berti; Elisabetta Mariavittoria Giunco; et al. (Antibiotics)
Background/Objectives: Antimicrobial stewardship programs (ASPs) optimize antimicrobial use, improving outcomes and reducing resistance. This study assessed the impact of a ward-specific ASP. Methods: A pre/post quasi-experimental study was conducted in an internal medicine ward at a tertiary hospital in Padua, Italy. During the intervention year (September 2023–August 2024), a multidisciplinary team (infectious disease consultants, pharmacists, microbiologists, nurses, and hygienists) held bi-weekly ward-based audits, reviewing antimicrobial prescriptions and performing bedside assessments. Therapy adjustments followed guidelines and local epidemiology. Educational sessions and infection prevention and control (IPC) protocols were also reinforced. Outcomes were compared to the previous year, considering patient characteristics. The primary outcome was antimicrobial consumption (DDD/100 patient days, DDD/100PD); secondary outcomes included cost savings, length of stay (LOS), and mortality. Results: Fifty audits assessed 1074 patients and 1401 antimicrobial treatments. Patient characteristics were similar. Antibiotic suspension or de-escalation occurred in 37.9% and 22% of patients, respectively. AWARE ACCESS class use increased (+17.5%), while carbapenem (−54.4%) and fluoroquinolone (−42.0%) use significantly declined (p < 0.05). IPC and microbiological culture guidance were provided in 12.1% of cases. Antimicrobial consumption dropped from 107.7 to 84.4 DDD/100PD (p < 0.05). No significant changes in LOS or mortality were observed. Antimicrobial costs fell by 48.8% (with EUR 57,100 saved). Conclusions: ASP reduced antimicrobial consumption, improved prescription quality, and cut costs without compromising patient outcomes. Multidisciplinary collaboration, audits, and education proved essential. Future studies should assess long-term resistance trends and integrate rapid diagnostics for enhanced stewardship.